Histological characterisation and prognostic evaluation of 62 gastric neuroendocrine carcinomas - Deng, Yujie; Chen, Xiaohui; Ye, Yuhong; Shi, Xi; Zhu, Kunshou; Huang, Liming; Zhang, Sheng; Ying, Mingang; Lin, Xuede (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: To determine the significance of expression of synaptophysin, chromogranin A, and Ki-67 and their association with clinicopathological parameters, and to find out the possible prognostic factors in gastric neuroendocrine carcinoma (G-NEC). Material and methods: We investigated the immunohistochemical features and prognosis of 62 G-NECs, and evaluated the association among expressions of synaptophysin, chromogranin A, and Ki-67, clinicopathological variables, and outcome. Results : Chromogranin A expression was found more commonly in small-cell NECs (9/9, 100%) than in large-cell NECs (27/53, 51%) (p = 0.008). No statistical significance was found in Ki-67 (p = 0.494) or synaptophysin (p > 0.1) expression between NEC cell types. Correlation analyses revealed that Ki-67 expression was significantly associated with mid-third disease of stomach (p = 0.005) and vascular involvement (p = 0.006), and hada trend of significant correlation with tumour relapse (p = 0.078). High expression of chromogranin A was significantly associated with histology of small-cell NECs (p = 0.008) and lesser tumour greatest dimension (p = 0.038). The prognostic significance was determined by means of Kaplan-Meier survival estimates and log-rank tests, and as a result, early TNM staging and postoperative chemotherapy were found to be correlated with longer overall survival (p < 0.05). Univariate analysis revealed associations between poor prognosis in NECs and several factors, including high TNM staging (p = 0.048), vascular involvement (p = 0.023), relapse (p = 0.004), and microscopic/macroscopic residual tumour (R1/2, p < 0.001). In a multivariate analysis, relapse was identified as the sole independent prognostic factor. Conclusions : No significant correlation between survival and expression of synaptophysin, chromogranin A, or Ki-67 has been determined in G-NECs. Our study indicated that early diagnosis, no-residual-tumour resection, and postoperative chemotherapy were possible prognostic factors.